Akibat Hukum Perusahaan Gagal Bayar Terhadap Nasabah Pemegang Polis - Kembaren, Keny Indah Gloria (Unram Law Review, 2023)
From January 2008 to September 2020, at least five life insurance companies failed to pay K Life Insurance (after this, referred to as "AJK"). AJK is a private company operating in the insurance sector under the K Group. In May 2020, the AJK company announced that the company was experiencing liquidity problems, so inevitably, payments for 2 AJK insurance products, including K Link Investa (after this referred to as "KLITA") and Protecto Investa K (after this referred to as "PIK") had to be paid and postponed as stated in the Decision on Ratifying the Peace Agreement (Homologation) Number 389/Pdt.Sus-PKPU/2020/PN-Niaga.Jkt.Pst. Several customers have signed a peace agreement with AJK, which contains a clause terminating the policy, resulting from which the agreement turns into an ordinary debt and receivables agreement. On the other hand, the company also needed help making payments for this insurance agreement. So, in this article, we will analyze the Legal Consequences of the Company’s Failure to Pay on Policy Holding Customers (Decision Study Number 647 K/PDT.SUS-PAILIT/2021). This writing is normative legal research. The research results show that the legal consequence of a company failing to pay is that the policyholder has the right to request a resolution of the problem outside of court, namely through LAPS-SJK. OJK also has the authority to punish insurance companies by limiting the business activities, giving written warnings, and revoking business licenses. The policyholder is permitted to file a lawsuit in court for non-compliance or broken promises made by the insurance company against him, namely not fulfilling the payment of benefits as agreed in the policy, and can also file a lawsuit for an unlawful act, as long as he can prove that the policyholder This policy is subject to losses caused by the insurance company. If the policyholder wants to seek resolution through bankruptcy/PKPU, they must request the OJK, and then the OJK will submit the request to the Commercial Court. When declared bankrupt, policyholders must be prioritized over other creditors.